Mass Customization Method For Higher Education - Saad, Saima; Abdullah, Ibrahim; Saad Khan, Muhammad (2010)
The idea of Mass customization in the education system is introduce. Customized education in an education system in which technologies and organizational skills are combining to provide for the individual’s educational needs, when and where they are required.Such a procedure seems to hold the promise of bridging the conflict between the need to react rapidly to changing knowledge-based skills on one hand and the relatively conservative social skills that the school has to provide. The present education system operates shop-mode,in which the single teacher is in charge of the complete cycle of education. No technology so far, including on-line and distant education has changed the shop-mode of the learning process. The paper discusses various aspects of modification that are needed in the educational system to implement the transition from the mass education to mass customized education for knowledge acquisition.These aspects include organization teacher’s attitude and the concept of two-tier classroom. The infra structure required for Mass customization Education to become operational is described; such infrastructure is based on ideas, which drive Mass customization in the production and business world.